No improvement in pregnancy and perinatal outcomes with combined luteal support in modified natural cycle frozen embryo transfer - Zhang, Wen; Wu, Sheling; Ren, Bingnan; Jia, Ruolin; Zhang, Wenjuan; Wang, Bijun; Du, Xiaofang; Guan, Yichun (Frontiers in Endocrinology, 2025)
ObjectiveWe investigated whether the addition of a luteal phase support drug benefits pregnancy and perinatal outcomes in modified natural-cycle frozen-thawed embryo transfer (mNC-FET) for women up to the age of 35 years.MethodsWe analyzed the clinical data of 3658 mNC-FET cycles of women up to the age of 35 years from the Reproductive Center of the Third Affiliated Hospital of Zhengzhou University from January 2018 to December 2020 in a retrospective cohort study. The cycles were divided into three groups based on the luteal phase support protocol used. The patients in group A received a combination of progesterone soft capsules and dydrogesterone (882 cycles), those in group B received dydrogesterone only (627 cycles), and those in group C received a combination of progesterone vaginal sustained-release gel and dydrogesterone (2149 cycles). Pregnancy and perinatal outcomes were compared among the three groups.ResultsLogistic regression analysis indicated that the three luteal phase support regimens were not associated with the live birth rate [OR(95% CI)B vs A=1.080, p=0.960; OR(95% CI)B vs C=0.252, p=0.291]. There were no significant differences in the newborn weight, premature delivery rate, pregnancy complications rate, and incidence of birth defects among the three groups.ConclusionsIn the mNC-FET cycle, patients under the age of 35 who chose dydrogesterone alone as a luteal phase support drug exhibited no difference in the live birth rate and perinatal outcome from patients who combined dydrogesterone with progesterone soft capsules or with progesterone vaginal sustained-release gel. However, the outcome still requires confirmation by large-sample prospective studies.